PEMETAAN PENGETAHUAN AWAL GURU: SUATU STRATEGI PEMDAMPINGAN DALAM MENULIS DAN MENERBITKAN BUKU - achmad dhany fachrudin; intan bigita kusumawati; siti nuriyatin; eka nurmala sari agustina; soffil widadah; dewi sukriyah; Lailatul Mubarokah; endang wahju andjariani (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
Teachers must have the skills to write textbooks. Teachers who write textbooks and use its in their learning can help them overcome learning problems. In addition, this textbook can increase teacher credit scores, academic promotion, and have economic value. However, not all teachers are able to write textbooks even to the process of publishing textbooks. Therefore, this community service activity aims to design a strategy through mapping teacher knowledge in writing and publishing textbooks. This activity was attended by teachers in the elementary and junior high schools in Integrated Islamic Education Institute Insan Kamil Sidoarjo. Teachers were given a basic knowledge questionnaire containing 12 statements of understanding about the preparation of textbooks and 2 statements regarding the legality of textbooks. The results of this activity, 1) teachers need to have knowledge in finding relevant references and ideas, 2) knowledge related to the components and flow of making textbooks, 3) understand the flow of publishing to ensure their textbooks can be published legally. Furthermore, the team developed a strategy to provide assistance in writing training seminars and publishing textbooks, includes 1) providing reinforcement of mastery of the material, 2) demonstrations to participants, 3) practice independently, and 4) monitoring.